Organizational Mortality: The Liabilities of Newness and Adolescence - Bruderl, Josef; Schussler, Rudolf (Administrative Science Quarterly, 1990)
This research has been supported by the Deutsche Forschungsgemeinschaft with grant Zi 207/5-1 (Project Leader: Prof. Dr. Rolf Ziegler). Thanks to the Munich Chamber of Commerce, which provided the data. Helpful comments, which greatly improved the quality of this paper, were given by Glenn Carroll, Michael Hannan, Peter Preisend6rfer, Thomas Voss, Gabriele Wiedenmayer, the editor of this journal, and especially by four anonymous referees. This article contains a theoretical discussion and an empirical test of Stinchcombe's liability of newness hypothesis, which assumes higher risks of failure for young organizations compared with old ones. It is shown that this hypothesis is not a good representation of the mortality hazard of West German business organizations. Therefore, we introduce the concept of a liability of adolescence, which proposes an inverted U-shaped risk pattern. It is shown that mortality, depending on the initial resource endowments of a firm, peaks between one and fifteen years after founding. From this perspective, extended interpretations of the liabilities of smallness and legal form are given. These arguments are-well supported by a log-logistic rate model estimated with our data.